The Relationship of Extracurricular Activities with Students' Character Education and Influencing Factors: A Systematic Literature Review - Ayu Puji Rahayu; Yinshi Dong (AL-ISHLAH: Jurnal Pendidikan, 2023)
Extracurricular activities are part of the school curriculum that has significant implications for adolescent development, improving academic achievement and character development. Extracurricular activities have significant implications for adolescent development, particularly for the central identity configuration process during this developmental phase. Not only for teenagers, well-organized extracurricular activities are also an essential part of a child's life; (2) Purpose of the Study: This study aims to determine the relationship between extracurricular activities and student character education and identify factors that can strengthen or weaken the relationship between the two; (3) Methods: This study aims to determine the relationship between extracurricular activities and student character education and identify factors that can strengthen or weaken the relationship between the two; (4) Results: The findings of this study show that extracurricular activities have a positive relationship with the development of student character education with several determinant factors that influence the relationship between the two, namely internal school factors such as friends, teachers, and school climate. All three are elements that exist in the school environment and are interrelated with each other. Meanwhile, the external factors of the school are parents. These two factors have a significant influence on the relationship between extracurricular activities and the development of character education.; and (5) Conclusions: The relationship between extracurricular activities and student character education is generally positive and mutually reinforcing.